The Correlation between Training, Career Development and Employee Performance with Moderating Variable of Job Satisfaction : A Case Study in Cambodia - Keomorakath PICH; Suhariadi Fendy (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
This study aims to determine employee training and career development and whether the employee is satisfied. The next objective is that the result of this study is to find out the positive relationship impact of training and career development on employee performance with job satisfaction as a moderating variable. This study aims to analyze the data collected from hundreds of respondents working in a company located in Phnom Penh City, Cambodia. The data have been analyzed, applying the statistical techniques SPSS program with correlation, simple regression, and multiple regressions. The research was conducted by a survey sample of the questionnaires according to the theory related to training, career development, employee performance, and job satisfaction online. This paper uses a Quantitative Method to analyze the phenomenon through all level staff working in the company. The research result includes suggestions and recommendations to the phenomenon, which will help management improve employee ability and capacity to work quality and achieve the company goal.